Drug utilisation trends in a physical rehabilitation hospital - Ljubojević, Gordana M.; Mastikosa, Milan; Dostanić Došenović, Tanja; Novaković Bursać, Snježana; Tomić, Nataša; Talić, Goran; Škrbić, Ranko; Stojiljković, Miloš P. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Drug utilisation monitoring could identify drug-related problems and hence improve the awareness of irrational drug use. The objective of this study was to analyse the drug utilisation patterns in a rehabilitation hospital over the period 2011–2016. Methods. The Anatomic Therapeutic Chemical classification/Defined Daily Dose (ATC/DDD) methodology was used to monitor the drug utilisation expressed as a number of DDD per 100 patient-days (HPD). The values of DDDs were obtained from the World Health Organisation (WHO) Collaborating Centre for Drug Statistics Methodology. Utilisation trends were analysed by means of the Compound Aggregate Growth Rate (CAGR), which is defined as an average annual change rate of some value during the period of interest. Results. The number of patient-days increased during the six years period; the CAGR being1.8% annually. At the same time, the total number of dispensed DDDs as well as the number of DDD/HPD decreased with the CAGR of -2.0% and -3.7% respectively. The average drug cost per patient-day varied from BAM 1.38 in 2013 to 0.95 in 2016; the CAGR being -1.8%. The most utilised drugs belonged to the ATC groups C, A, B, M and N and they contributed to an average of 77% of all drugs used each year. On the top of the list of most utilised drugs were: hydroxocobalamin, thioctic acid, enalapril, diclofenac, amlodipine, acetylsalicylic acid, pantoprazole, paracetamol and bromazepam. Conclusions. The overall drug utilisation in the hospital was modest and almost equal in 2016 compared to 2011. Besides the leading consumption of vitamin B12 and thioctic acid, this study points out some interesting prescribing patterns, such as predominant use of diclofenac over ibuprofen, and overuse of proton pump inhibitors. There is a need for educative interventions among physicians in order to improve their prescribing practice.
Keywords: hospitals; physical and rehabilitation medicine; drug therapy; drug utilisation